A heuristic method for reactive power planning - Mantovani, JRS; Garcia, A. V. (Institute of Electrical and Electronics Engineers (IEEE), 1996)
An approach for solving reactive power planning problems is presented, which is based on binary search techniques and the use of a special heuristic to obtain a discrete solution. Two versions were developed, one to run on conventional (sequential) computers and the other to run on a distributed memory (hypercube) machine. This latter parallel processing version employs an asynchronous programming model. Once the set of candidate buses has been defined, the program gives the location and size of the reactive sources needed(if any) in keeping with operating and security constraints.
Keywords: reactive power planning; parallel processing; binary search; heuristic methods